Deregulated Sex Chromosome Gene Expression with Male Germ Cell-Specific Loss of Dicer1 - Greenlee, Anne R.; Shiao, Meng-Shin; Snyder, Elizabeth; Buaas, F. William; Gu, Tongjun; Stearns, Timothy M.; Sharma, Manju; Murchison, Elizabeth P.; Puente, Gabriella C.; Braun, Robert E. (PLOS ONE, 2012)
MicroRNAs (miRNAs) are a class of endogenous, non-coding RNAs that mediate post-transcriptional gene silencing by inhibiting mRNA translation and promoting mRNA decay. DICER1, an RNase III endonuclease encoded by Dicer1, is required for processing short 21–22 nucleotide miRNAs from longer double-stranded RNA precursors. Here, we investigate the loss of Dicer1 in mouse postnatal male germ cells to determine how disruptions in the miRNA biogenesis pathway may contribute to infertility. Reduced levels of Dicer1 transcripts and DICER1 were confirmed in germ cell knock-out (GCKO) testes by postnatal day 18 (P18). Compared to wild-type (WT) at 8 weeks, GCKO males had no change in body weight; yet showed significant reductions in testis mass and sperm number. Histology and fertility tests confirmed spermatogenic failure in GCKO males. Array analyses at P18 showed that in comparison to WT testes, 75% of miRNA genes and 37% of protein coding genes were differentially expressed in GCKO testes. Among these, 96% of miRNA genes were significantly down-regulated, while 4% miRNA genes were overexpressed. Interestingly, we observed preferential overexpression of genes encoded on the sex chromosomes in GCKO testes, including more than 80% of previously identified targets of meiotic sex chromosome inactivation (MSCI). Compared to WT, GCKO mice showed higher percentages of germ cells at early meiotic stages (leptotene and zygotene) but lower percentages at later stages (pachytene, diplotene and metaphase I) providing evidence that deletion of Dicer1 leads to disruptions in meiotic progression. Therefore, deleting Dicer1 in early postnatal germ cells resulted in deregulation of transcripts encoded by genes on the sex chromosomes, impaired meiotic progression and led to spermatogenic failure and infertility.